Financing climate change mitigation measures in South African Local Government - Mashamaite, M. M. (International Conference on Public Administration and Development Alternatives, 2018)
A transition from energy intensive economy to green economy requires a notable capital investment in addition to the capital required by municipalities for provision of services needed to meet development goals. Green infrastructure investments will need approximately USD$5.3 trillion to effect climate change mitigation actions globally. This paper reviewed literature, paying attention to the financing of climate change mitigations within the local government with special reference to one South African Metropolitan Municipality, the City of Tshwane Metropolitan Municipality. The City of Tshwane Metropolitan Municipality relies on public finance sources which are insufficient to achieve the development goals and address the climate change issues through green projects. The review of literature revealed that local governments across the globe prefers green finance as an alternative financing source for funding green projects. Accessing private sources of capital is a challenge for the local governments due to lack of adequate skills for preparing projects, poor good governance practices and poor credit rating. This paper employs a qualitative approach and focuses on the financing of climate change mitigation measures at a local level. The paper concludes that if local government can establish innovative measures to attract financing for green projects and such will close the financing gap. Keywords: Climate change, Development goals, Green finance, Local government, Mitigations
Article published in: The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Climate change; Development goals; Green finance; Local government; Mitigations; Climate change mitigation; Climatic changes -- Risk management